Policy options to reduce deforestation - Angelsen, A. (Center for International Forestry Research, 2009)
Four types of policies could reduce deforestation: policies to depress agricultural rent, policies to increase and capture forest rent, policies that directly regulate land use, and cross-sector policies that underpin the first three. While payments for environmental services (PES) have clear advantages, in the early stages of REDD+ implementation, broader policies which address underlying causes are more feasible and likely to be more successful. REDD+ is a new direction in forest conservation. This means that countries need to take into account research on deforestation, and lessons learned from previous forest conservation policies, when developing national REDD+ strategies.